(untitled) (Eurasian Medical Research Periodical, 2022)
During this global pandemic of COVID-19 infection, it became well known that morbidity and mortality is especially high at the extreme of life. This is presumed due to low immunity associated with other comorbid conditions like diabetes, hypertension, cardiovascular disease, obesity and metabolic syndrome. But the information available on the immune status of COVID-19 patients is limited. Adaptive response of increased CD8+ levels in COVID-19 patients seems to be useful in mild cases where it causes deteriorating effects in progressed severe disease patients resulting in destruction of type 2 pneumocytes hence inability to regenerate the alveolar epithelium. A phenomenon called cytokine storm activates violent immunological reactions in the lung tissue resulting in ARDS followed by multiple organ system damages in COVID-19 patients. Immune response to novel coronavirus is complex, involves both innate and adaptive immunity, and is biphasic. Significant differences were observed when comparing severe and non-severe patients. Analysis of the reported results from clinical trials clearly show an involvement of specific cellular immunity (predominantly leucopenia, decreased counts of CD3+, CD4+, and CD8+ T lymphocytes, changes of T cell compartment) and the so-called cytokine storm, which is associated with worsening of symptoms and the promotion of lung damage. An interesting finding regarding eosinopenia that can have both diagnostic and prognostic value is reported by some authors. Examination of selected immune parameters could help to identify severe patients with the risk of unfavorable course of the disease, predict the prognosis and recognize improvement in the clinical status